Torg’s ratio in normal adult nepalese population - Rijal, Badri; Pokharel, R K; Paudel, S; Shah, L L (Journal of Society of Surgeons of Nepal, 2017)
Introduction: Acute cervical trauma occasionally leads to cervical canal stenosis in some individuals in spite of minor trauma. The spinal canal-to-vertebral body ratio (Torg-Pavlov ratio) has been proposed for assessing developmental spinal canal stenosis. It is not affected by magnification, and is measured on lateral plain films of cervical vertebrae. The result of this study may help in better understanding of the Torg’s ratio, which is more reliable than direct measuring of the mid-sagittal diameter of the cervical spinal canal in the diagnosis of cervical spinal stenosis or predicting the prognosis of cervical spinal cord injury. If Torg’s ratio is below normal there is risk of cervical cord injury whereas relatively safe in large Torg’s ratio. Torg’s ratio can be accessed even in rural areas where x-rays are easily available and more economical than MRI and CT scan. It can assess the risk of cord injury during sports and outdoor activities and help individuals’ choose safe carrier in sports or others activities. Methods: In order to ascertain the normal values of the Torg’s ratio in adults Nepalese, hundred sets of cervical vertebral columns of hundred adult Nepalese population of age group 20-40 years were examined. Consecutive patients presenting with history of neck pain with normal x-ray findings or history of trauma without cervical spine injury from Orthopaedic OPD (out patients department) and emergency department of Tribhuvan University Teaching Hospital, Maharajgunj, Kathmandu from March 2011 to August 2012 were included in the study. Results: There were 48 males and 52 females with age ranging from 20 yrs to 40 yrs with the mean of 30.34±5.36 years. The normal average canal/body ratio of the cervical spine is 0.99 +/- 0.09 in male and 1.01 +/- 0.07 in female. It was observed that the ratio of the antero-posterior diameters of cervical spinal canal and vertebral bodies showed sexual dimorphism. Conclusion: The Torg’s ratio is the same irrespective of gender and height. The result of this study will help in better understanding of the Torg’s ratio, which is more reliable than direct measuring of the mid-sagittal diameter of the cervical spinal canal in the diagnosis of cervical spinal stenosis or predicting the prognosis of cervical spinal cord injury. JSSN 2015; 18 (1), Page: 5-9